Pelatihan Membuat Media Pembelajaran Berbasis Wordpress Dengan Plugin H5p Kepada Jurusan Teknik Jaringan Komputer Dan Telekomunikasi Kelas XI Di SMKN 1 Pandeglang - Reihan Mutaqin; Popi Dayurni; Ade Fricticarani; Kurniati Rahmadani; Ayu Trisnawati; Nunung Nuraeni; Nova Amelia Putri; Izatul Khaeriyah (Institut Nalanda, 2024)
Technology-based learning media plays a crucial role in supporting the learning process in the current digital era. This article describes the implementation of training for creating learning media based on WordPress, utilizing the H5P plugin in the Computer Network and Telecommunication Engineering Department for Grade XI at SMKN 1 Pandeglang. The training aims to enhance students' skills in developing interactive learning content.